(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
We explained the successful fields of artificial intelligence in the empirical scientific evidence in the form of a conceptual model. The method used in the research was a systematic review (standard PRISMA). The field of research was the scientific articles related to artificial intelligence and its effectiveness in human learning, published in the years 2018 to 2022. We extracted articles from authentic databases such as Science Direct, Elsevier, Scopus, Eric, and Springer. We examined them with careful evaluation criteria and were sixty - five articles ready to enter the analysis. The results showed that 5 applicationand s in the field of artificial intelligence application in human learning can be extracted and explained, which is: The field of detection and identification, and field of expansion and optimization, the field of design and implementation and, evaluation, The field of psychological support, The field of supporting teacher activities. Below we explained the results with empirical evidence and made suggestions.